A Vesicular Arbuscular Mycorrhizal Fungus (Glomus intraradix) Induces a Defense Response in Alfalfa Roots. - Volpin, H. (1994)
Flavonoid accumulation and activities of phenylalanine ammonia-lyase (PAL), chalcone isomerase (CHI), and chitinase were followed during early colonization of alfalfa roots (Medicago sativa L. cv Gilboa) by vesicular arbuscular (VA) fungi (Glomus intraradix). Formononetin was the only flavonoid detected that showed a consistent increase in the inoculated roots. This increase depended only on the presence of the fungus in the plant rhizosphere; no colonization of the root tissue was required. CHI and chitinase activities increased in inoculated roots prior to colonization, whereas the increase in PAL activity coincided with colonization. After reaching a maximum, activities of all enzymes declined to below those of uninoculated roots. PAL inactivation was not caused by a soluble inhibitor. Our results indicate that VA fungi initiate a host defense response in alfalfa roots, which is subsequently suppressed.